EKSISTENSI HUKUM ISLAM DALAM KANCAH HUKUM NASIONAL - Hamdan Arief Hanif; Aisyah Nurhana (Universitas Darunnajah Jakarta, Indonesia, 2023)
Indonesia is a state of law as affirmed in the results of the amendment to the 1945 Constitution Article 1 paragraph (3). The law became a milestone in the life of Indonesian society. Almost all aspects of life should be regulated in national law so that there are guidelines for action. The development of this national law must contain elements that can protect the needs and rights of the community, one of which is the religious aspect. Islamic law is also one of the sources of substance of Indonesian national law because the majority of the Indonesian population are followers of Islam. This article seeks to discuss Islamic laws that later had an influence on Indonesian national law. The method used in this study is descriptive research. Descriptive research is a research step carried out by providing research in the form of an effort to describe a symptom, event, and event that occurs.